Mesenteric venous thrombosis as a rare complication of decompression sickness - Satoshi Toyota; Shigeyuki Nagata; Shinichiro Yoshino; Sota Kono; Syogo Kawanami; Syohei Maeda; Erina Kuramitsu; Michihiro Ichimannda; Satoko Nagamatsu; Seiichiro Kai; Yasuro Fukuyama; Hiroyuki Orita; et al. (Surgical Case Reports)
Abstract Background Decompression sickness (DCS) induced by extravascular and intravascular gas bubbles during decompression can present with varying manifestations, such as joint pain, numbness, cutaneous symptoms, and cardiopulmonary dysfunction. However, mesenteric venous thrombosis (MVT) is a rare complication of DCS. To the best of our knowledge, only a few cases have been reported, and surgical cases of MVT secondary to DCS have not yet been reported. Case presentation A 59-year-old man who was a fisherman and recreational diver dived to a depth of 100 feet. After diving, he noted abdominal and postcervical pain and visited a community hospital. Computed tomography (CT) revealed a large amount of intravenous gas, so he was diagnosed with DCS. He was then transferred to a previous hospital, where hyperbaric oxygen therapy (HBOT) was performed. HBOT reduced the amount of venous gas, but his abdominal pain worsened, so he was transferred to our hospital. CT showed pneumatosis cystoides intestinalis. Because of the possibility of intestinal necrosis, a laparoscopic examination was performed, which revealed necrosis of the transverse colon. We therefore performed a transverse colon resection. He was discharged 36 days after the surgery and followed an uneventful postoperative course. Conclusions DCS is likely to cause MVT. If intestinal necrosis is suspected, a laparoscopic examination may be useful for determining the diagnosis and treatment. MVT should be included as a differential diagnosis of abdominal pain that persists after HBOT.